Conflictos familiares y su incidencia en el desarrollo emocional en un caso atendido en el DECE - Cedeño Álvarez, Tanya Thalya (2020)
The objective of this case study was to describe the incidence of family conflicts in the emotional development of a nine-year-old child treated in the DECE department of the “Adolfo María Astudillo” educational unit, since these were reflected in classes, I have emotional symptoms, sadness, isolation and because of this the failure to fulfill their tasks. Affected some areas at social, family and educational level. Through the collection of information from the clinical history, test and interviews, the diagnosis of family dysfunctionality was obtained. And in turn demonstrate that parents' family conflicts affect the emotional development of the patient. Therefore, it is expected that the proposal made with systemic family approaches will be effective in helping to improve the family and emotional relationships of the child.